Synthesis and biological evaluation of hydantoin derivatives as potent antiplasmodial agents - Mohd Azlan Nafiah (Tanjung Malim, 2024)
Synthesis and biological evaluation of hydantoin derivatives as potent antiplasmodial agents by Mohd Azlan Nafiah